Health and well‐being in adolescent survivors of early childhood cancer: a report from the Childhood Cancer Survivor Study. Issue 3 (4th October 2013) - Mertens, Ann C.; Brand, Sarah; Ness, Kirsten K.; Li, Zhenghong; Mitby, Pauline A.; Riley, Anne; Patenaude, Andrea Farkas; Zeltzer, Lonnie
Abstract Objective With the growing number of childhood cancer survivors in the US, it is important to assess the well‐being of these individuals, particularly during the transitional phase of adolescence. Data about adolescent survivors' overall health and quality of life will help identify survivor subgroups most in need of targeted attention to successfully transition to adulthood. Participants and methods This ancillary study to the Childhood Cancer Survivor Study focused on children 15‐19 years of age who had been diagnosed with cancer before the age of 4 years. A cohort of siblings of pediatric cancer survivors of the same ages served as a comparison sample. Adolescent health was assessed using the Child Health and Illness Profile‐Adolescent Edition (CHIP‐AE) survey. Results The teen survey was sent to 444 survivor teens and 189 siblings. Of these, 307(69%) survivors and 97 (51%) siblings completed and returned the survey. The overall health profiles of siblings and survivors were similar. Among survivors, females scored significantly below males on satisfaction, discomfort, and disorders domains. Survivors diagnosed with central nervous system tumors scored less favorably than leukemia survivors in the global domains of satisfaction and disorders. Conclusion In general, adolescent survivors fare favorably compared to healthy siblings. However, identification of the subset of pediatric cancer survivors who are more vulnerable to medical and psychosocial disorders in adolescence provides the opportunity for design and implementation of intervention strategies that may improve quality of life. Copyright © 2013 John Wiley & Sons, Ltd.